Decreased iron absorption in patients with active rheumatoid arthritis, with and without iron deficiency. Issue 5 (May 1988) - Weber, J; Werre, J M; Julius, H W; Marx, J J
Abstract : Mucosal uptake, mucosal transfer, and retention of a physiological dose of ferrous iron were studied in women with active rheumatoid arthritis (RA): 19 with normal and 17 with depleted bone marrow iron stores. Control subjects were 26 normal women and 20 women with uncomplicated iron deficiency. Iron absorption was measured with 59Fe as a tracer and by whole body counting. Compared with controls, final iron retention was considerably decreased in both groups of patients with RA. Analysis of the two sequential steps of iron absorption showed that mucosal uptake was normal in iron replete patients with RA but was significantly lower in patients with RA with depleted iron stores compared with iron deficient controls. Mucosal transfer of iron was considerably decreased in patients with RA with normal iron stores. The impaired absorption of iron in patients with active RA may delay the correction of the haemoglobin concentration when anaemia of chronic disease is complicated by iron deficiency.